Study on characteristics of oil and gas occurrence and reservoir space of medium-high maturity continental shale—A case study of middle jurassic lianggaoshan formation in fuling block, southeast of sichuan basin, south China - Yuan, Xuejiao; Zhang, Kun; Peng, Jun; Li, Bin; Han, Fengli; Chen, Xuecheng; Zheng, Zehao; Ruan, Jingru; Ye, Laiting; Wang, Zeyun; Huang, Zhen; Chen, Kun; et al. (Frontiers in Earth Science, 2022)
Possessed of easy access to development and fair economic benefits, medium-high maturity continental shale oil and gas have become the focus of shale oil and gas study in the future. Shale oil and gas mainly occur in pores, but studies on the pore characteristics of shale oil and gas occurrence are by no means sufficient. Focused on shale from the Middle Jurassic Lianggaoshan Formation in Well TYX, Fuling block, southeast of Sichuan Basin where a breakthrough in shale oil and gas exploration was recently achieved, this study selects core samples and conducts a series of analyses, including vitrinite reflectance analysis, kerogen microscopic examination experiment, total organic carbon (TOC) content analysis, mineral composition analysis, gas content measurement, isothermal adsorption experiment, S1 content analysis, and others. The analyses are to identify the pore characteristics of the continental medium and high maturity shale oil and gas by virtue of scanning electron microscope (SEM) with Ar-ion milling and the image processing software ImageJ. The conclusions are drawn as follows: in terms of lithofacies, medium-high maturity continental shale oil and gas mainly occur in organic-rich clay shale and organic-rich mixed shale; with regard to material composition, shale oil and gas mainly occur in organic matter, illite-smectite mixed layers and illite. Shale adsorbed gas content accounts for at most 40% of the total shale gas content and shale free gas content takes up at least 60% of the total shale gas content. Pores of solid bitumen, solid bitumen-clay mineral complex mass, clay minerals, structured vitrinite, and funginite are mostly developed in shale. Among them, the first three types of pores are the main reservoir space in shale considering their large number, good roundness, medium pore diameter, fairly good roundness of pore edges, and the complex shapes which altogether contribute to the large surface porosity.